Formation kinetics of Maillard reaction intermediates from glycine–ribose system and improving Amadori rearrangement product through controlled thermal reaction and vacuum dehydration. (1st May 2020) - Zhan, Huan; Tang, Wei; Cui, Heping; Hayat, Khizar; Hussain, Shahzad; Tahir, Muhammad Usman; Zhang, Songlin; Zhang, Xiaoming; Ho, Chi-Tang
Highlights: Amadori compound formation is the dominant reaction in vacuum dehydration. Controlled thermal reaction and vacuum dehydration improve Amadori compound yield. Reaction temperature and time are key factors to control byproduct content. Abstract: Amadori rearrangement product (ARP) is an ideal flavor precursor. The formation kinetics of ARP from glycine–ribose system, 3-deoxyribosone (3-DR) and 1-deoxyribosone (1-DR) were evaluated, and then controlled thermal reaction (CTR) coupled with vacuum dehydration was proposed to improve the ARP yield. As key factors controlling the formation of byproducts, CTR temperature and time were optimized as 100 °C, 60 min based on the formation kinetics of the ARP and deoxyribosones. Vacuum dehydration was further used to increase the ARP yield from 0.77% to 64.50%, which was improved by 82.8 times, while 3-DR and 1-DR yield increased only by 1.5 and 3.7 times, respectively. The formation of ARP was the dominant reaction during vacuum dehydration. Under optimal conditions, CTR coupled with vacuum dehydration was an effective method to control byproducts formation and improve the ARP yield simultaneously. This method may offer a potential application in flavor enhancement of light-color food.